Konsumsi Energi, Pembangunan Sektor Keuangan dan Emisi Karbon di Indonesia - Karunia, Monica Ruth; Komarulzaman, Ahmad; Tjahjawandita, Ari (UI Scholars Hub, 2023)
This study investigates EKC hypothesis in Indonesia over the period of 1980–2019. Within the EKC framework, we examine the impact of GDP, energy consumption, and financial development on CO2 emissions using ARDL bound-test. The results show that the study variables are cointegrated, representing a long-run relationship. The EKC hypothesis is not validated as we found a U-shaped relationship. Given the turning point (IDR13,274,579) has been reached in 1987, a further increase in GDP would only be associated with an increase in CO2 emissions. While energy consumption increases CO2 emissions, financial development seems to improve environmental quality by lowering CO2 emissions.